Effect of aminergic signaling on the humoral innate immunity response of Drosophila - Cattabriga, Giulia; Giordani, Giorgia; Gargiulo, Giuseppe; Cavaliere, Valeria (Frontiers in Physiology, 2023)
Biogenic amines are crucial signaling molecules that modulate various physiological life functions both in vertebrates and invertebrates. In humans, these neurotransmitters influence the innate and adaptive immunity. In this work we analyzed whether the aminergic neurotransmission of dopamine, serotonin and octopamine could have an impact on the humoral innate immune response of Drosophila melanogaster. This is a powerful model system widely used to uncover the insect innate immunity mechanisms which are also conserved in mammals. We found that the neurotransmission of all these amines positively modulates the Toll-responsive antimicrobial peptide (AMP) drosomycin (drs) gene in adult flies infected with Micrococcus luteus bacteria. Indeed, we showed that either by blocking the neurotransmission in their specific aminergic neurons by expressing Shibirets (Shits) or silencing by RNAi the vesicular monoamine transporter gene (dVMAT), caused a significantly reduced expression of the Toll responsive drs gene. However, upon Micrococcus luteus infection the block of aminergic transmission did not alter the expression of AMP attacin genes responding to the immune deficiency (Imd) and Toll pathways. Overall, our results reveal a neuroimmune function for the biogenic amines in the humoral immunity, but also further highlight the complexity of the network controlling AMP gene regulation.